Mussolini's nation-empire : sovereignty and settlement in Italy's borderlands, 1922-1943 - Pergher, Roberta (New studies in European history, 2019)
Roberta Pergher transforms our understanding of Fascist rule. Examining Fascist Italy's efforts to control the antipodes of its realm - the regions annexed in northern Italy after the First World War, and Italy's North African colonies - she shows how the regime struggled to imagine and implement Italian sovereignty over alien territories and peoples. Contrary to the claims of existing scholarship, Fascist settlement policy in these regions was not designed to solve an overpopulation problem, but to bolster Italian claims to rule in an era that prized self-determination and no longer saw imperial claims as self-evident. Professor Pergher explores the character and impact of Fascist settlement policy and the degree to which ordinary Italians participated in and challenged the regime's efforts to Italianize contested territory. Employing models and concepts from the historiography of empire, she shows how Fascist Italy rethought the boundaries between national and imperial rule